Her unlikely protector - Black, Regan (Black, Regan. Escape Club heroes., 2021)
"She keeps her heart to herself, but a new case changes everything ... Officer Aubrey Rawlins has learned the hard way -- trusting people only ends in disaster. So when Leo Butler shows up in her precinct, claiming his sister has gone missing, she remains sympathetic but detached. As danger stalks the investigating pair, she's unsure if what's growing between them is real. But can Aubrey open up to let in her unexpected protector?"--Back cover.